Surface roughness of resin-based composites Subjected to professional prophylaxis - João Lacerda Neto; José Alejandro Castro González; Matheus de Paula Costa; Leticia de Andrade Balardini; Marissol Fernandes Oliveira; Marina Amaral; Rayssa Ferreira Zanatta (Revista da Faculdade de Odontologia de Porto Alegre)
Aim: This study evaluated the effect of two prophylaxis methods over the surface roughness of different resin composites. Materials and Methods: Ten disc-shaped specimens (7 mm x 2 mm) were made for each composite tested: MH - microhybrid composite with regular viscosity (Opallis); NH – nanohybrid composite with regular viscosity (Vittra APS); BF – high-viscosity bulk fill composite (Opus Bulk Fill); MHF - microhybrid flowable composite (Opallis flow); and OS – nanohybrid one-shade composite with regular viscosity (Vittra Unique). Initial roughness (Ra) values were obtained from each sample, and then they were divided into two groups (n = 5) following the prophylaxis method: SB – prophylaxis with sodium bicarbonate powder (125µm grain) using an air-powder polishing device (30 s application distanced 10 mm with 2 bar); and PP – prophylaxis with pumice paste and rotatory brush (30 s, 3000 rpm and pressure of 150 g). After that, a new Ra measurement (Raf) was obtained, and the difference was calculated (ΔRa). Data were compared using Three-way ANOVA followed by Bonferroni teste and the Ra difference (ΔRa) was analyzed by Two-way ANOVA followed by the Tukey test (p<0.05). Results: MHF presented higher Ra values after receiving prophylaxis with SB, while for NH, the abrasion with pumice increased the Ra, and for the other groups, no differences were found. Discussion: Alteration promoted by prophylaxis is material dependent. Conclusion: Professional prophylaxis with a bicarbonate jet or abrasion with pumice-based paste can induce changes in the composites' roughness.